2019
DOI: 10.7717/peerj.6246
|View full text |Cite
|
Sign up to set email alerts
|

A new segmentation algorithm for measuring CBCT images of nasal airway: a pilot study

Abstract: BackgroundThree-dimensional (3D) modeling of the nasal airway space is becoming increasingly important for assessment in breathing disorders. Processing cone beam computed tomography (CBCT) scans of this region is complicated, however, by the intricate anatomy of the sinuses compared to the simpler nasopharynx. A gold standard for these measures also is lacking. Previous work has shown that software programs can vary in accuracy and reproducibility outcomes of these measurements. This study reports the reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…But a substantially lower accuracy was found in volume calculation, with a little underestimated volume compared to direct measurement (Table ). This was consistent with the previous reports by Zhang et al, who demonstrated greatly overestimated volume of nasal cavity with measurement errors + 3.9% in the left side and 7.6% in the right side when segmenting nasal airway . An explanation for this could be the limitation of semi‐automated segmentation method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But a substantially lower accuracy was found in volume calculation, with a little underestimated volume compared to direct measurement (Table ). This was consistent with the previous reports by Zhang et al, who demonstrated greatly overestimated volume of nasal cavity with measurement errors + 3.9% in the left side and 7.6% in the right side when segmenting nasal airway . An explanation for this could be the limitation of semi‐automated segmentation method.…”
Section: Discussionmentioning
confidence: 99%
“…No correlation was found between the mean and the difference of the four variables from the plots, and the results were uniformly distributed within the limits of agreement, which demonstrated that there existed a consistent agreement between the two methods. 19 An explanation for this could be the limitation of semi-automated segmentation method. Small edges could be removed by morphology operation or multiple slice edit manually.…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, the segmentation could be completed within 1 hour, which is considerably less compared to a fully manual segmentation, 5 although comparable with what was reported in the literature for semiautomatic segmentation. 14,15 Volume measurements for the NC demonstrated good correlation coefficients and low measurement errors, indicating excellent intraexaminer and interexaminer reliabilities.…”
Section: Discussionmentioning
confidence: 86%
“…1,12 OSA is suggested to be related to a PA anatomic disorder 13 so that the treatment options are mostly associated with enlarging the PA. 12 CBCT scans taken for orthodontic purposes represent a low-dose 3D radiological record facilitating the To date, several authors have reported methods to measure the NC. 6,14,15 However, automatic segmentation methods using commercial dental software were reported to be inaccurate. 16 In this study, the masks were sketched manually every 10 slides and then a semiautomatic procedure was followed.…”
Section: Discussionmentioning
confidence: 99%
“…Following an extensive literature research, we have given the ICC values of 5 studies that compared the segmentation of AI and ground truth in Table 4 . ICC values were reported as 0.899 by Zhang et al 45 , 0.977 by Leonardi et al 46 , 0.985 by Sin et al 12 , 0.986 by Park et al 47 . Shujaat et al 48 provided precision, recall, accuracy, dice, intersection over union values in their study as 0.97 ± 0.01, 0.96 ± 0.03 1.00 ± 0.00 0.97 ± 0.02 and 0.93 ± 0.03, respectively.…”
Section: Discussionmentioning
confidence: 97%